The Impact of Service Quality, Medical Personnel Communication, and Facility Availability on Patient Satisfaction with Patient Economic Perceptions as Moderating Variables - Indinastin, Indinastin; Suhardi, Suhardi; Amin, Mat; Firdaus, Rahmad (Lembaga Riset Mutiara Akbar (LARISMA), 2025)
This study aims to analyze the influence of service quality, interpersonal communication of medical personnel, and facility availability on patient satisfaction at Pangkalpinang City General Hospital (RSUD Kota Pangkalpinang), as well as to examine the mediating role of patients' economic perception. A quantitative approach was employed through a survey method involving 218 outpatient and inpatient respondents. Data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the SmartPLS 4 application. The results indicate that service quality, interpersonal communication, and facility availability have a positive and significant effect on patient satisfaction. Furthermore, patients’ economic perception significantly mediates the relationship between service quality and interpersonal communication with patient satisfaction, but does not significantly mediate the relationship between facility availability and patient satisfaction. These findings underscore the importance of improving service quality and interpersonal communication, as well as strengthening patients’ economic perception to optimize patient satisfaction in hospitals. This research provides practical implications for hospital management in designing more holistic and patient-oriented service quality improvement strategies.